RELATIONSHIP BETWEEN MATERNAL NUTRITIONAL KNOWLEDGE AND CHILDREN GROWTH UNDER 5 YEARS OF AGE IN LAKHODAIR COMMUNITY, LAHORE, PAKISTAN - BIBI , N; IFTIKHAR , K; FATIMA , A; AKMAL , A; AKBAR , T; ZAFAR , M; FIRDOUS , U (Biological and Clinical Sciences Research Journal, 2024)
Nutrition knowledge is essential for the prevention of nutrition-related problems. Knowledge is a familiarity, awareness, or understanding of someone or something, such as facts, information, descriptions, or skills, which is acquired through experience or education by perceiving, discovering, or learning. Objective: To determine the relationship between maternal nutritional knowledge and children’s growth under 5 years of age in the Lakhodair community, Lahore Pakistan. Methods: A quantitative correlational study design was used to conduct this study. The study duration was 4 months after IRB approval. This study was conducted in the Lakhodair community in Lahore, Pakistan. Study Population females (mothers) living in the Lakhodair community in Lahore, Punjab Pakistan. A simple random sampling technique was used for the selection of sample size. Results: Results revealed that all participants had breastfed their child. The majority (90%) of the participants didn’t rate their knowledge so it was compromised by their attitude problems and lack of awareness regarding maternal nutritional guidelines. More than 72% have no access to the resources.68% responded that child eating habits are not average depicting mal-nutrition. P value was less than 0.05 showing the significant relation of maternal knowledge with children’s growth. Conclusion: It was concluded that maternal nutritional knowledge has a positive and direct relation with the child’s growth. As the mother’s knowledge increases ultimately practices will be better and consequently, maternal nutritional knowledge and childcare practices will significantly impact the child’s growth.